Revitalization Concept Patirtan Sites as a Sustainable Spiritual Tourism in Malang, East Java - Junianto, Junianto; Srilestari, Rosalia Niniek; Subadyo, A. Tutut (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2019)
The Patirtan site is a legacy of the ancient Singhasari kingdom in Malang, has a high historical value. The existence of the Patirtan site is related to the source of holy water (amerta), and is considered sacred by the community. The use and development of the Patirtan site has tended to be partial and contrary to the concept of conservation. The revitalization of Patirtan site in Malang is the use of historical heritage in the form of bathing pools, for religious self-cleaning activities. Spiritual tourism activities, as a form of human relations with God, through traditional rituals, occur at the sites of temples and Patirtan in Malang, East Java. Spiritual tourism actors in several Patirtan sites in the Malang region are the preserver of the Nusantara culture, originating from Java and Bali. This revitalization study, carried out by descriptive method, through fact-finding with proper interpretation of people's attitudes, people's spiritual behavior and phenomena on the Patirtan site. There are three cases of Patirtan site in Malang, which is quite significant to be used as a spiritual tourism destination, namely Sumberawan Temple, Patirtan Watugede and Widodaren water source. Through historical studies, exploring ritual activities at Patirtan sites in Malang, then analyzing the physical character and function of Patirtan's sites, the concept of revitalization was then formulated.Â DOI: https://doi.org/10.26905/lw.v11i2.2954